'It's possibly made us feel a little more alienated': How people from ethnic minority communities conceptualise COVID-19 and its influence on engagement with testing. Issue 2 (April 2022) - Vandrevala, Tushna; Alidu, Lailah; Hendy, Jane; Shafi, Shuja; Ala, Aftab
Objectives: The cultural beliefs, practices and experiences of ethnic minority groups, alongside structural inequalities and the political economy play a critical, but overlooked role in health promotion. This study aimed to understand how ethnic minority groups in the United Kingdom conceptualised COVID-19 and how this influenced engagement in testing. Method: Black (African and Caribbean) and South Asian (Indian, Pakistani and Bangladeshi) community members were purposefully recruited from across the UK. Fifty-seven semi-structured interviews were conducted and analysed using principles of grounded theory. Results: We found that people of Black and South Asian ethnicity conceptualised COVID-19 as a disease that makes them visible to others outside their community and was seen as having more severe risk and suffering worse consequences, resulting in fear, stigmatisation and alienation. Views about COVID-19 were embedded in cultural beliefs, relating to culturally specific ideas around disease, such as ill-health being God's will. Challenges brought about by the pandemic were conceptualised as one of many struggles, with the saliency of the virus contextualised against life experiences. These themes and others influenced engagement with COVID-19 testing. Testing was less about accessing timely and effective treatment for themselves and more about acting to protect the family and community. Testing symbolised a loss of income, anxiety and isolation, accentuated by issues of mistrust of the system and not being valued, or being treated unfairly. Conclusion: Health communications should focus on counterbalancing the mistrust, alienation and stigmatisation that act as barriers to testing, with trust built using local credible sources.